Introduction to Financial Accounting U.S. GAAP Adaptation - Annand, David; Marchand, Donna; Dauderis, Henry (Open textbook library., 2019)
This textbook is an adaptation by D. Marchand and Athabasca University of the original text written by D. Annand and H. Dauderis. It is intended for use in entry-level college and university courses in financial accounting. A corporate approach is utilized consistently throughout the book. The adapted textbook includes multiple ancillary student and instructor resources. Student aids include solutions to all end-of-chapter questions and problems, and randomly-generated spreadsheet problems that cover key concepts of each chapter. These provide unlimited practice and feedback for students. Instructor aids include an exam bank, lecture slides, and a comprehensive end-of-term case assignment. This requires students to prepare 18 different year-end adjusting entries and all four types of financial statements, and to calculate and analyze 16 different financial statement ratios. Unique versions can be created for any number of individual students or groups. Tailored solutions are provided for instructors. Another version of the textbook written by D. Annand and adapted by T. Thompson, including .docx files and ancillary material, can be obtained upon request to D. Annand (davida@athabascau.ca).